The role of business subsidies in job-creation start-ups, gazelles and imcumbents - Heli Koski; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2011)
Our data concerning the whole Finnish company population from the years 2003-2008 suggest that the impacts of business subsidies on employment growth differ more between high-growth start-ups and other firms than between start-ups and over five years old incumbents. All subsidies seem to relate positively to the contemporary employment growth both among start-ups and incumbents. Furthermore, our data show that both the employment of start-ups and older incumbents receiving employment or other subsidies grow more than that of non-subsidized firms after subsidy reception. Instead, we find that business subsidies do not provide significant further boost for the contemporary or after-subsidy growth of gazelles. There are apparently some other factors dominating the growth of young high-growth firms making them to grow strongly, in many cases, with or without subsidies.
Keywords: J23; L10; O33; 330; public subsidies; technology policy; growth; Finland; Unternehmensfinanzierung; Subvention; Beschäftigungseffekt; Forschungs- und Technologiepolitik; Finnland